Factors Affecting the Effectiveness of CBT Implementation in Student Learning Evaluation Using UTAUT: A Case Study at SMAS Katolik Sint Pieter Waikabubak - Marlina Dama Lero; Ardiyanto Dapadeda; Maria Wilda Malo (International Journal Software Engineering and Computer Science (IJSECS), 2026)
This study examines the digital transition in the student learning evaluation system at SMA Katolik Sint Pieter Waikabubak through the adoption of a Computer-Based Test (CBT) application. Although CBT has been in use since 2023, persistent issues — including unstable internet connections and limited exam monitoring features — have raised legitimate questions regarding its operational effectiveness. This study aims to evaluate the effectiveness of CBT in student learning assessments and to identify the factors that shape students' behavioral intention to use the system. A quantitative approach grounded in the Unified Theory of Acceptance and Use of Technology (UTAUT) was applied. The findings demonstrate that CBT adoption has measurably improved the transparency and accuracy of learning evaluations. Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions each exert a statistically significant effect on students' intention to use CBT, with Perceived Usefulness emerging as the strongest predictor. Age and gender were found to moderate several of these relationships. The results indicate that adequate school infrastructure and an accessible application interface are decisive factors in the success of exam digitization. Schools are advised to continue strengthening their technical and physical support systems to sustain long-term adoption of this technology.